Comercio electrónico como herramienta para mejorar el desempeño de la Empresa Importadora Farmacéutica Jorua de la ciudad de Babahoyo periodo 2021. - Contreras Vera, Juan Ariel (2022)
Electronic commerce is a business model that has come to complement the traditional form of sales by businesses and which has had to be constantly updated due to technological advances. This model offers great benefits for both companies and customers, since organizations invest fewer resources, and in the case of customers, they receive adequate attention when purchasing or contracting a product or service. This study is based on the theme of electronic commerce as a tool to improve the performance of a company. For this research, the pharmaceutical importing company Jorua was taken, in which the main problem was a reduction in clients in the importing company, for which it seeks to improve the electronic commerce tool that serves to improve the performance and productivity of this company, was based on the information of authors as a guide for the development of electronic commerce and with a type of descriptive methodology with a technique such as the survey through a questionnaire made to the users. usual costumers